Community-Based Organic Agriculture in the Philippines. (December 2015) - Suh, Jungho
This paper explores institutional mechanisms that might be required to boost both organic agriculture and rural development in the Philippines. Special attention is paid to community-based organic agriculture as a pathway to rural development. The Philippines has two decades of experience of community-based natural resource management. Unlike public natural resources such as forests, watersheds or fisheries, however, the community-based organic agriculture programme is intended to deal with the private property regime. Thus, if the programme is to be successful, agrarian land reform must continue. Integrated rice–duck farming is among the suitable and viable options for organic agriculture, given that rice is a major agricultural crop and duck meat is popular in the Philippines. Area-based organic food certification systems need to be formulated and a government–farmers partnership should be forged to facilitate farmers' access to domestic and international organic food markets.